Portraits of the brazilian soul:: the songs of Guinga and Aldir Blanc: - Chequetto, João Victor Castro (Revista do Colóquio, 2024)
This article aims to explore dialogues and connections between the songs of composer and guitarist Carlos Althier de Souza Lemos Escobar, known as Guinga, and the lyrics of poet, writer, and composer Aldir Blanc Mendes, focusing on the idea of Brazilian soul and national identity. For this discussion, excerpts from two songs by the partnership of Guinga and Aldir from the album Delírio Carioca (1993) have been selected: “Visão de Cego” and “Baião de Lacan.” These songs reveal a series of musical and poetic characteristics that resonate with the notion of Brazilian-ness. To support this dialogue, I will reference other authors who also discuss the works of both composers and their intrinsic relationship with Brazilian identity.